FOXG1 promotes aging inner ear hair cell survival through activation of the autophagy pathway. Issue 12 (2nd December 2021) - He, Zu-Hong; Li, Ming; Fang, Qiao-Jun; Liao, Fu-Ling; Zou, Sheng-Yu; Wu, Xia; Sun, Hai-Ying; Zhao, Xue-Yan; Hu, Yu-Juan; Xu, Xiao-Xiang; Chen, Sen; Sun, Yu; et al.
ABSTRACT: Presbycusis is the cumulative effect of aging on hearing. Recent studies have shown that common mitochondrial gene deletions are closely related to deafness caused by degenerative changes in the auditory system, and some of these nuclear factors are proposed to participate in the regulation of mitochondrial function. However, the detailed mechanisms involved in age-related degeneration of the auditory systems have not yet been fully elucidated. In this study, we found that FOXG1 plays an important role in the auditory degeneration process through regulation of macroautophagy/autophagy. Inhibition of FOXG1 decreased the autophagy activity and led to the accumulation of reactive oxygen species and subsequent apoptosis of cochlear hair cells. Recent clinical studies have found that aspirin plays important roles in the prevention and treatment of various diseases by regulating autophagy and mitochondria function. In this study, we found that aspirin increased the expression of FOXG1, which further activated autophagy and reduced the production of reactive oxygen species and inhibited apoptosis, and thus promoted the survival of mimetic aging HCs and HC-like OC-1 cells. This study demonstrates the regulatory function of the FOXG1 transcription factor through the autophagy pathway during hair cell degeneration in presbycusis, and it provides a new molecular approach for the treatment of age-related hearing loss. Abbreviations : AHL: age-related hearing loss; baf: bafilomycin A1; CD: common deletion; D-gal: D-galactose; GO: glucose oxidase; HC: hair cells; mtDNA: mitochondrial DNA; RAP: rapamycin; ROS: reactive oxygen species; TMRE: tetramethylrhodamine, ethyl ester